2017
DOI: 10.18844/prosoc.v4i9.3046
|View full text |Cite
|
Sign up to set email alerts
|

The impact of smart board usage on class management

Abstract: Recent technological developments have made access to information easy. Today, countries are giving shape to their educational policies by including information technologies in their education systems. One of the information technologies that are in wide use is smart boards. This research aims to determine the positive and negative impacts of smart board usage on class management. The difficulties teachers experience in class management, skills of teachers in terms of ensuring motivation in the class, their le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The teacher directs the training processes for necessary effective classroom management. Today, the necessity of teachers to be effective in classroom management and the management of learners' unwanted behaviors are an important aspect (Karadag, 2018). Research on classroom management has shown that teachers may face difficulties while managing unwanted behaviors.…”
Section: Teachers' Classroom Management Proficiency In Public Element...mentioning
confidence: 99%
See 1 more Smart Citation
“…The teacher directs the training processes for necessary effective classroom management. Today, the necessity of teachers to be effective in classroom management and the management of learners' unwanted behaviors are an important aspect (Karadag, 2018). Research on classroom management has shown that teachers may face difficulties while managing unwanted behaviors.…”
Section: Teachers' Classroom Management Proficiency In Public Element...mentioning
confidence: 99%
“…Many definitions have been used in the literature to refer to classroom management, and it is observed that the classroom is generally shaped within these concepts. For example, according to Karadag (2018), classroom consists of the activities relevant to the regulation, control and alteration of the learning environment and student behaviors to realize teaching and learning activities in line with predetermined goals in the classroom.…”
Section: Introduction Background Of the Studymentioning
confidence: 99%
“…These results imply that technology can be successfully employed as a means to enhance student motivation and comprehension, particularly in educational settings where intricate and abstract concepts are taught in subjects like science. The integration of smart boards in science education has proven to have significant benefits for both teachers and students (Yiğit, Yılmaz, & Karakaş, 2017) Interactive Whiteboards and Smartboards significantly enhance teaching science concepts by promoting engagement, enabling multimedia presentations, and fostering interactive learning sessions (Gündüz & Kutluca, 2019;Karadag, Koc, & Kalkan, 2017;Perinpasingam, Arumugam, Subramaniam, & Mylvaganam, 2014). However, it's essential to ensure they are used effectively to aid, not replace, traditional teaching methods.…”
Section: Interactive Whiteboards and Smartboardsmentioning
confidence: 99%
“…The teacher directs the training processes for necessary effective classroom management. Today, the necessity of teachers to be effective in classroom management and the management of students' unwanted behaviors are an important aspect (Karadag, 2018). Research on classroom management has shown that teachers may face difficulties while managing unwanted behaviors.…”
Section: Introductionmentioning
confidence: 99%